Chemical constituents, clinical efficacy and molecular mechanisms of the ethanol extract of Abelmoschus manihot flowers in treatment of kidney diseases. (27th July 2020) - Li, Nan; Tang, Haitao; Wu, Liang; Ge, Haitao; Wang, Yurong; Yu, Honglin; Zhang, Xiuli; Ma, Jimei; Gu, Harvest F.
Abstract : Abelmoschus manihot, also called as "Huangkui" in Chinese, is an annual flowering herb plant in the family of Malvaceae. As a traditional Chinese medicine, the ethanol extract of the flower in Abelmoschus manihot is made as Huangkui capsule and has been used for medication of the patients with kidney diseases. Its efficacy in clinical symptoms is mainly improving renal function and reducing proteinuria among the patients with chronic kidney disease, diabetic kidney disease or IgA nephropathy. The possible mechanism of Huangkui capsule treatment in kidney diseases may include reducing inflammation and anti‐oxidative stress, improving immune response, protecting renal tubular epithelial cells, ameliorating podocyte apoptosis, glomerulosclerosis and mesangial proliferation, as well as inhibiting renal fibrosis. In this review, we first described chemical constituents and pharmacokinetic characteristics in ethanol extract of the flower of Abelmoschus manihot . We then summarized the clinical and epidemiological relevancies of kidney diseases particularly in the mainland of China and discussed the possible molecular mechanisms of Huangkui capsule in the treatment of kidney diseases. Finally, we prospected further research on cellular and molecular mechanisms and application of this Chinese natural medicine in kidney diseases.